2017
DOI: 10.4172/2155-9899.1000510
|View full text |Cite
|
Sign up to set email alerts
|

CD30 Expression vs. Serum Soluble CD30 (sCD30) Level: Role in Prognosis and Treatment of Acute Myeloid Leukaemia

Abstract: Objectives: As we noted that CD30 is a valuable molecule in regulation of growth and death of lymphocytes in malignant lymphomas, we analyzed CD30 expression and serum soluble CD30 (sCD30) molecule level in patients with acute myeloid leukemia (AML) to assess their role as a prognostic markers and to examine the possibility of anti-CD30 to be a targeted therapy in these patients. Methods:We studied CD30 expression by Multicolor flow cytometry immunophenotypic analysis on bone marrow aspirates of 50 AML patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…A meta-analysis study also found that high serum CD30 levels were a predictor factor of poor prognosis in patients with Hodgkin's lymphoma which is quite different from our study. [ 16 ] The serum CD30 level decreases with the treatment of the disease and returns to its highest levels in case of relapse. [ 17 ] As we showed CD30 positive patients had lower MRD, it might be a good prognostic factor and a positive indicator of treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis study also found that high serum CD30 levels were a predictor factor of poor prognosis in patients with Hodgkin's lymphoma which is quite different from our study. [ 16 ] The serum CD30 level decreases with the treatment of the disease and returns to its highest levels in case of relapse. [ 17 ] As we showed CD30 positive patients had lower MRD, it might be a good prognostic factor and a positive indicator of treatment response.…”
Section: Discussionmentioning
confidence: 99%